Construction of TRIF-knockout NA and BHK-21 cell lines and effect on rabies virus proliferation efficiency - Weitao HUANG; Jiaqi LI; Yao PENG; Xiangping YIN; Xiaofeng GUO; Jun LUO (Huanan Nongye Daxue xuebao)
ObjectiveTo construct TIR-domain-containing adaptor-inducing interferon β (TRIF) gene knockout mouse NA cell line and hamster BHK-21 cell line using CRISPR/Cas9 technology, evaluate the proliferative capacity of rabies virus (RABV) in these knockout cell lines, and investigate TRIF function during RABV infection. Method First, single guide RNA (sgRNA) was designed, and recombinant plasmids pSpCas9-NA-TRIF-KO and pSpCas9-BHK-21-TRIF-KO were constructed for TRIF gene knockout. After plasmid transfection, positive cells were preliminarily screened using puromycin followed by single-cell subclone isolation through limited dilution. The expanded cell populations were subsequently validated by PCR amplification, sequencing, and Western blot identification, TRIF-knockout NA and BHK-21 cell lines were established. Standard challenge strain CVS-11 and vaccine strain BNSP-SAD of RABV were then inoculated into both knockout and wild-type cells. Viral N protein expression levels were detected by Western blot, and viral titers were determined through TCID50 assay to evaluate rabies virus proliferation efficiency in different cell lines. ResultThe recombinant plasmids pSpCas9-NA-TRIF-KO and pSpCas9-BHK-21-TRIF-KO for TRIF-knockout were successfully constructed, the TRIF-knockout NA and BHK-21 cell lines were screened and identified. Compared with the wild-type cell line, the expressions of N proteins in two TRIF-knockout cell lines inoculated with RABV CVS-11 and BNSP-SAD were obviously elevated after 24 h infection, and the virus titer significantly increased after 24 h infection. ConclusionRABV has superior proliferation capacity in TRIF-knockout cell lines compared to wild-type counterparts, and TRIF may have the ability to inhibit viral replication. The findings not only provide substantial support for further investigation of TRIF function, but also establish novel cellular models for RABV cultivation and research.